Parenting Stress During the COVID‐19 Outbreak: Socioeconomic and Environmental Risk Factors and Implications for Children Emotion Regulation. Issue 2 (28th September 2020) - Spinelli, Maria; Lionetti, Francesca; Setti, Annalisa; Fasolo, Mirco
Abstract : The COVID‐19 outbreak imposed to Italian families many changes in their daily life increasing the risk of developing psychological problems. The present study explored risk factors associated with parenting stress and implications for children's emotion regulation in families with different socioeconomic risks. Parents of 2–14 years old children completed a survey reporting difficulties experienced due to the lockdown, level of household chaos, parenting stress, parent involvement in the child's daily life, and children emotion regulation competences. The general mean levels of parenting stress and children emotion regulation abilities were not at clinical level compared with Italian norms. Household chaos predicted higher levels of parenting stress, which, in turn, was associated with less effective emotion regulation in children through the mediating role of parental involvement. More stressed parents were less involved in their children's activities, decreasing children's effective emotion regulation. Only for SES no‐risk families, the lockdown constraints increased parenting stress. For SES at‐risk families, the impact of parenting stress and involvement on children regulation strategies was stronger, with a protective role played by parental involvement on children's negativity not evident for SES no‐risk families. Dealing with the lockdown is a stressful experience for parents who have to balance personal life, work, and children upbringing, without other help. This situation potentially impairs their ability to be supportive caregivers and is consequently detrimental for children well‐being. Policies should take into consideration the implications of the lockdown for families' mental health and tailor supportive interventions according to family's risk factors. Resumen: El brote de la COVID‐19 impuso a las familias italianas muchos cambios en su vida cotidiana, los cuales aumentaron el riesgo de desarrollar problemas psicológicos. El presente estudio analizó los factores de riesgo asociados con el estrés de la crianza y las consecuencias para la regulación emocional de los hijos en familias con diferentes riesgos socioeconómicos. Un grupo de padres de niños de entre dos y 14 años contestó una encuesta donde informó las dificultades vividas debido al confinamiento, el nivel de caos en el hogar, el estrés en la crianza, la participación de los padres en la vida diaria de los hijos y las competencias de los hijos para regular sus emociones. Los niveles promedio generales de estrés en la crianza y las habilidades de regulación emocional en los niños no estuvieron a nivel clínico en comparación con las normas italianas. El caos en el hogar predijo niveles más altos de estrés en la crianza, el cual, a su vez, estuvo asociado con una menor regulación emocional eficaz en los niños mediante el rol mediador de la participación de los padres. Los padres más estresados participaron menos en las actividades de sus hijos, lo cual disminuyó la regulación emocional eficaz en los niños. Solo en los casos de las familias sin riesgo socioeconómico las limitaciones del confinamiento aumentaron el estrés en la crianza. Para las familias de riesgo socioeconómico, el efecto del estrés en la crianza y la participación en las estrategias de regulación emocional de los niños fue más profundo, y en el caso de las familias sin riesgo socioeconómico, no se evidenció el papel protector desempeñado por la participación de los padres en la negatividad de los niños. Lidiar con el confinamiento es una experiencia estresante para los padres que tienen que compatibilizar la vida personal, el trabajo y la educación de los niños sin ninguna otra ayuda. Esta situación puede deteriorar su capacidad de ser cuidadores comprensivos y, como consecuencia, ser perjudicial para el bienestar de los niños. Las políticas deberían tener en cuenta las consecuencias del confinamiento en la salud mental de las familias y adaptar intervenciones de apoyo de acuerdo con los factores de riesgo de las familias. 摘要: 新冠肺炎疫情给意大利家庭的日常生活带来许多变化，增加了出现心理问题的风险。本研究探讨不同社会经济风险家庭中，与父母压力相关的风险因素及它们对儿童情绪调节的影响。2至14岁儿童的父母完成了一项调查，报告了由于禁闭、家庭混乱程度、父母压力、父母参与儿童日常生活和儿童情绪调节能力所经历的困境。与意大利标准相比，养育压力和儿童情绪调节能力的一般平均水平没有达到临床水平。家庭混乱预示着更高程度的父母压力，反过来，通过父母参与的中介作用，孩子的情绪调节能力更低。父母压力越大，参与孩子活动就越少，孩子有效情绪调节能力就越弱。只有对没有社会经济地位风险的家庭来说，禁闭才会增加养育子女的压力。在有社会经济地位风险的家庭中，父母的压力和参与对儿童调节策略的影响更大，而父母参与对儿童消极情绪的保护作用在没有社会经济地位风险的家庭中并不明显。 对于那些不得不在没有其他帮助的情况下平衡个人生活、工作和抚养孩子的父母来说，应对禁闭是一件很有压力的事情。这种情况可能损害他们成为支持性照顾者的能力，因此对儿童的福祉有害。政策应考虑到封锁对家庭心理健康的影响，并根据家庭的风险因素制定支持性干预措施。